The Role of Communication in Social Change: Promoting Societal Transformation - Iba, La; Larisu, Zulfiah; Irwanto, Irwanto; Joko, Joko (PT. Hafasy Dwi Nawasena, 2024)
Social change is an inevitable phenomenon in people's lives, and communication has a very important role in driving this transformation. In this context, communication is not just an exchange of information, but also a process that can influence the way of view, values, and norms that exist in society. This research aims to explore the role of communication in social change, focusing on how communication can be a tool to facilitate the transformation of society at various levels. Through the Systematic Literature Review (SLR) approach, this study collects and analyzes various literature that discusses the relationship between communication and social change. The results of this study show that effective communication can contribute to positive changes in society, including increasing social awareness, promoting community participation, and encouraging collaboration between various stakeholders. The study also identifies several challenges faced in the communication process that can hinder desired social change. By understanding the dynamics of communication in the context of social change, this study hopes to provide recommendations for policymakers, social activists, and communication practitioners to design more effective communication strategies in driving social transformation. At the end of this study, it is hoped that a deeper understanding of the importance of communication in creating sustainable social change will be realized.